Biological characterization of avian osteopetrosis. - Banes, A J (1977)
Chicks infected as 12-day-old embryos with an end-point purified derivative of avian myeloblastosis virus developed a rapidly progressive osteopetrosis that manifested within 1 week of hatching. A detailed comparison of osteopetrotic chicks and normal hatchmates revealed the following. (i) Osteopetrotic chicks exhibited a stunting syndrome, growing at a mean rate that was 26% of the control rats. (ii) At autopsy, the mass of the lymphoid organs was reduced, whereas the mass of the heart, pancreas, kidneys, lungs, brain, liver, and bones of osteopetrotic chicks was increased. Edema was likely responsible for most of the increase in organ weight. (iii) Infected chicks exhibited a normochromic, normocytic anemia that was virus dose dependent and was not required for the development of osteopetrosis. (iv) Bone collagen content was normal. (v) Osteopetrotic bone was initially hypomineralized, but later became more fully mineralized. (vi) The concentrations of alpha, beta, and gamma globulins in the plasma were elevated in osteopetrotic chicks, whereas albumin concentration was decreased. (vii) The level of plasma alkaline phosphatase was elevated in osteopetrotic chicks, yet the level of acid phosphatase was unchanged. (viii) Body and bone temperatures were unchanged.